M2 macrophage-derived extracellular vesicles protect against abdominal aortic aneurysm by modulating macrophage polarization through miR221-5p - Yang Ma; Xiang-jiu Ding; Si-yu Lu; Xiao-fang Huang; Yuan-yuan Hu; Han Liu; Bin Liu; Ke-yin Liu; Ming-xiang Zhang; Hao Wang; Feng Xu; Wei-dong Qin (Cellular & Molecular Biology Letters)
Abstract Background Extracellular vesicles (EVs) derived from M2 macrophages (M2-EVs) play a protective role in the pathogenesis of acute lung injury. However, their roles and mechanisms in abdominal aortic aneurysm (AAA) are unknown. Methods The effects of M2-EVs in AAA were examined in ApoE−/− mice with angiotensin II infusion. After M2 macrophages were stimulated with antisense oligonucleotides of miR221-5p (miR221-5p-ASOs), EVs were extracted and administered to mice via the tail vein. In vitro, the primary bone marrow-derived monocytes (BMDMs) were isolated and co-cultured with human aortic endothelial cells (HAECs) in Transwell chambers. Results M2-EVs significantly reduced AAA incidence and maximal aortic diameters, improved fiber continuity, increased α-SMA, and reduced macrophage infiltration in AAA mice. RNA sequencing revealed that miR221-5p was upregulated in M2-EVs and downregulated in AAA. miR221-5p-ASOs reduced the protection of M2-EVs in AAA mice. M2-EVs induced M2 macrophage polarization, while miR221-5p-ASOs had no effect. Moreover, M2-EVs alleviated oxidative stress and inflammatory responses in HAECs. Mechanistically, miR221-5p bound to poly(ADP-ribose) polymerase 1 (PARP-1) mRNA and reduced PARP-1 expression; PARP-1 was bound to protein phosphatase 1ɑ (PP-1ɑ) and negatively regulated its expression. In vitro experiments showed miR221-5p modulated macrophage polarization through the PARP-1/PP-1ɑ/JNK/c-Jun pathway. Macrophage deletion of PARP-1 inhibited AAA formation and phosphorylation of JNK/c-Jun in mice. Conclusions miR221-5p in M2-EVs plays a critical role in AAA pathophysiology by modulating macrophage polarization through PARP-1/PP-1ɑ/JNK/c-Jun signaling. M2-EVs and miR221-5p represent promising therapeutic options for AAA.